Non-woven fabric and surface sheet for absorbent article using same
By reducing the density in the thickness direction of the non-woven fabric, controlling the fineness and fiber density of the composite fibers, and adopting a non-pressure heat-suspended process, the existing non-woven fabrics have been solved in terms of hand feeling and soft permeability, and the effect of excellent hand feeling and soft permeability is achieved.
Patent Information
- Application Number
- CN202380061844.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-27
- Filing Date
- 2023-07-21
- Publication Date
- 2025-04-04
AI Technical Summary
The existing non-woven fabrics used for surface materials of absorbent articles have shortcomings in taking into account both the feel and the permeability of soft stools. Hot air non-woven fabrics have problems such as damage to the hand and blockage of soft stools. Although the finer composite fibers improve the permeability of soft stools, the feel is reduced.
By reducing the density in the thickness direction of the nonwoven fabric, the fiber density of the composite fiber is controlled to be between 3.0 dtex and 6.0 dtex, the fiber density of the high-density part is 13.0 pieces/mm2 or less, and the fiber density ratio between the high-density part and the low-density part is 1.4 or less, and a non-pressure heat-supporting process is used to form a follow-up point of intersection.
The non-woven fabric has achieved a significant improvement in soft stool permeability while maintaining a good feel, avoiding blockage problems caused by uneven fiber density, and the feel of the hand is not easily damaged when using high-fine composite fibers.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to a nonwoven fabric having both a good hand feel and soft stool permeability, and a surface sheet for an absorbent article using the nonwoven fabric. Background Art
[0002] Nonwoven fabrics used as surface sheets for absorbent articles such as disposable diapers and sanitary napkins are being improved to provide greater comfort. In particular, surface sheets for absorbent articles such as diapers are required to have excellent hand feel and the ability to quickly transport liquids or solid substances with different viscosities such as urine, soft stools, or menstrual blood to the absorbent body (liquid permeability).
[0003] As a non-woven fabric used for surface materials such as absorbent articles, hot air non-woven fabrics are known. The so-called hot air non-woven fabric is obtained by heat treating a web containing composite fibers composed of at least two thermoplastic resins with different melting points. As a method for heat treating a web, for example, a method of heat-bonding composite fibers to each other by a heat treatment device (for example, a hot air through-type heat treatment machine, a hot air blowing type heat treatment machine) including a transport support for supporting and transporting the web is disclosed (for example, Patent Document 1). However, since the hot air non-woven fabric is manufactured by blowing hot air, the pressure generated by the hot air is applied to the web, so that a non-woven fabric with different fiber densities on the upper and lower sides can be obtained. As a result, in addition to the damage to the hand feel of the non-woven fabric, there is also a problem that soft stools will be blocked in the part with high fiber density. In addition, the soft stool permeability can be improved by increasing the fineness of the composite fiber used for the hot air non-woven fabric, but if a composite fiber with a large fineness is used, there is a problem of decreased hand feel.
[0004] In addition, Patent Document 2 discloses a nonwoven fabric having openings provided between convex portions protruding toward the skin-facing side as a surface sheet of an absorbent article. In this case, soft feces discharged in the form of a surface sheet are retained between the convex portions of the sheet, which not only causes discomfort to the wearer, but also requires the formation of a complex structure such as concave-convex or openings, which increases the manufacturing cost.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2019-80907
[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-68382 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The present invention was completed based on the above-mentioned prior art, and its purpose is to provide a nonwoven fabric, a surface sheet for an absorbent article, and an absorbent article that have a simple structure and have both a soft feel and soft stool permeability.
[0011] Technical means of solving problems
[0012] The inventors of the present invention have repeatedly conducted diligent research to solve the above-mentioned problem and believe that the blockage of soft stool can be eliminated by reducing the fiber density of the high-density part, thereby obtaining excellent soft stool permeability. However, it is known that if the fiber fineness used is increased in order to reduce the fiber density of the high-density part, the soft stool permeability tends to be improved, but it is not sufficient. In addition, the friction between the fiber with a large fineness and the skin is large, and the feel is impaired. In view of these conditions, the inventors of the present invention have conducted further research. As a result, it is found that by reducing the density in the thickness direction of the nonwoven fabric, the soft stool permeability is greatly improved, and even if the fiber with a large fineness is used, the feel is not easily impaired, thereby completing the present invention.
[0013] That is, the present invention has the following structure.
[0014] [1] A nonwoven fabric comprising composite fibers whose intersections are thermally bonded, wherein the composite fibers have a fineness of 3.0 dtex to 6.0 dtex, and the fiber density of a high-density portion of the nonwoven fabric is 13.0 fibers / mm 2 Hereinafter, the fiber density ratio between the high-density portion and the low-density portion in the nonwoven fabric is 1.4 or less.
[0015] [2] The nonwoven fabric according to [1], wherein the fiber density of the high-density portion is 5.5 fibers / mm 2 ~8.0 roots / mm 2 .
[0016] [3] The nonwoven fabric according to [1] or [2], wherein the conjugate fiber has a fineness of 4.5 dtex to 6.0 dtex.
[0017] [4] The nonwoven fabric according to any one of [1] to [3], wherein the strength per unit area weight of the nonwoven fabric is 1.00 N / 50 mm to 1.50 N / 50 mm.
[0018] [5] A surface sheet for an absorbent article, comprising the nonwoven fabric according to any one of [1] to [4].
[0019] [6] An absorbent article according to any one of [1] to [4].
[0020] Effects of the Invention
[0021] According to the present invention, a nonwoven fabric, a surface sheet for an absorbent article, and an absorbent article having a simple structure and having both a good texture and soft stool permeability can be provided. DETAILED DESCRIPTION
[0022] The nonwoven fabric of the present invention is characterized in that it contains composite fibers whose intersections are thermally bonded, the fineness of the composite fibers is 3.0 dtex to 6.0 dtex, and the fiber density of the high-density portion of the nonwoven fabric is 13.0 fibers / mm 2 Hereinafter, the fiber density ratio between the high-density portion and the low-density portion is 1.4 or less.
[0023] (Composite Fiber)
[0024] The composite fiber used in the nonwoven fabric of the present invention is not particularly limited as long as it can be melted by heat to form a bonding point, and examples thereof include concentric sheath-core composite fibers, eccentric sheath-core composite fibers, or parallel composite fibers. In addition, the cross-sectional shape of the composite fiber is not particularly limited, and any of a circular shape such as a circle or an ellipse, a triangular shape such as a square, a star shape or an octagonal shape, a split shape or a hollow shape can be used.
[0025] The thermoplastic resin constituting the composite fiber is not particularly limited, and examples thereof include polyethylene resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), or high-density polyethylene (HDPE), polypropylene resins such as crystalline polypropylene (PP) or copolymers of propylene and α-olefin (excluding propylene) (copolymerized polypropylene (Co-PP)) having propylene as the main component, polyethylene terephthalate (PET), polybutylene terephthalate, copolymerized polyethylene terephthalate (Co-PET), polyester resins such as polylactic acid, polyglycolic acid, or polybutylene succinate, polyvinyl alcohol resins, polyvinyl acetate resins, acrylic resins, polystyrene resins, polyurethane resins, polyamide resins, or fluorine resins. Among them, polyethylene resin, polypropylene resin, or polyester resin is preferably used as a surface sheet for absorbent articles. The combination of thermoplastic resins constituting the composite fiber is not particularly limited, but preferably has a melting point difference of 10°C or more, and more preferably has a melting point difference of 20°C or more. As specific combinations of high melting point components / low melting point components of thermoplastic resins, PP / HDPE, PP / LLDPE, PP / Co-PP, PET / HDPE, PET / LLDPE, PET / Co-PET, and PET / PP can be exemplified, but from the perspectives of feel, raw material cost, and production safety, a combination of PP / HDPE or PET / HDPE is preferred, and a combination of PET / HDPE is more preferred. In addition, from the perspective of thermal bonding, it is preferred that the low melting point component accounts for more than 50% of the surface of the composite fiber, and more preferably accounts for more than 70%.
[0026] In addition, the volume ratio of the low melting point component to the high melting point component is not particularly limited, but if the ratio of the low melting point component is large, the strength of the bonding points between the composite fibers is improved, thereby tending to obtain a nonwoven fabric with high strength, and if the ratio of the high melting point component is large, the hand feel of the nonwoven fabric or fiber product tends to be improved. From this viewpoint, the volume ratio of the low melting point component to the high melting point component is preferably 20 / 80 to 80 / 20, and more preferably 30 / 70 to 70 / 30.
[0027] The thermoplastic resin constituting the composite fiber may contain additives such as antioxidants, light stabilizers, ultraviolet absorbers, neutralizers, nucleating agents, epoxy stabilizers, lubricants, antibacterial agents, deodorants, flame retardants, antistatic agents, pigments, or plasticizers as needed within the range that does not hinder the effects of the present invention.
[0028] The fineness of the composite fiber used in the nonwoven fabric of the present invention is 3.0 dtex to 6.0 dtex, preferably 4.5 dtex to 6.0 dtex. If the fineness of the composite fiber is 3.0 dtex or more, the fiber density of the nonwoven fabric can be reduced, thereby obtaining a nonwoven fabric with excellent soft stool permeability, and if it is 6.0 dtex or less, a nonwoven fabric with excellent hand feel can be obtained.
[0029] The fiber length of the composite fiber is not particularly limited, but is preferably 20 mm to 102 mm, and more preferably 30 mm to 51 mm. If the fiber length is 20 mm to 102 mm, a web having excellent openability or texture can be easily formed in a web forming process based on a carding method, etc., and a nonwoven fabric having uniform physical properties can be obtained.
[0030] (Non-woven fabric)
[0031] The nonwoven fabric of the present invention is characterized in that it contains composite fibers whose intersections are thermally bonded, the fineness of the composite fibers is 3.0 dtex to 6.0 dtex, and the fiber density of the high-density part of the nonwoven fabric is 13.0 fibers / mm 2 In the conventional method of thermally bonding the intersections of the composite fibers by blowing hot air, the fiber density of the high-density part of the nonwoven fabric can be 13.0 fibers / mm by increasing the fineness of the fibers used. 2 In addition, in the method of compaction treatment using a hot roller, the fiber density ratio of the high-density part to the low-density part can be less than 1.4, but the fiber density will exceed 13.0 fibers / mm 2 , and satisfactory soft stool permeability cannot be obtained. In contrast, in the present invention, it is found that by heat bonding the intersections of composite fibers with a fineness of 3.0 dtex to 6.0 dtex under non-pressure, it is possible to simultaneously meet the fiber density of the high-density part of the nonwoven fabric of 13.0 fibers / mm 2 The fiber density ratio of the high-density portion to the low-density portion is set to 1.4 or less, thereby significantly improving the soft stool permeability while maintaining the existing feel.
[0032] Here, the so-called "high-density area" and "low-density area" in this specification refer to the upper and lower areas divided into three equal parts in the thickness direction of the non-woven fabric. When the fiber density is measured, the one with a higher fiber density is called the "high-density area", and the one with a lower fiber density is called the "low-density area".
[0033] In addition, the "fiber density" in this specification is represented by the number of fibers per unit area in the cross section of the nonwoven fabric, and the unit can be, for example, fibers / mm 2 The method for measuring the fiber density is described in detail in the examples.
[0034] The fiber density of the high-density portion of the nonwoven fabric of the present invention is 13.0 fibers / mm 2 Below, preferably 12.0 / mm 2 Below, more preferably 8.0 pieces / mm 2 If the fiber density is 13.0 fibers / mm 2 On the other hand, the lower limit of the fiber density in the high-density part is not particularly limited, but from the viewpoint that the number of fibers in contact with each other becomes sufficient and the fuzzing is suppressed and the nonwoven fabric with good hand feel can be obtained, the fiber density in the high-density part is preferably 5.5 fibers / mm 2 In addition, as for the fiber density of the low-density part, as long as the ratio of the fiber density of the high-density part to the low-density part satisfies 1.4 or less, that is, as long as it is 3.9 fibers / mm 2 ~13.0 roots / mm 2 That's it.
[0035] The fiber density ratio of the high-density part and the low-density part in the nonwoven fabric of the present invention is 1.4 or less, preferably 1.3 or less, more preferably 1.2 or less. If the fiber density ratio of the high-density part and the low-density part is 1.4 or less, even if the composite fiber with a smaller fineness is used, the fiber density of the high-density part of the nonwoven fabric will not become too large, and the blockage of the soft stool at the high-density part can be suppressed. In addition, even if the composite fiber with a larger fineness is used, the hand feel is not easily damaged. In the case of a nonwoven fabric whose fiber density ratio of the high-density part and the low-density part exceeds 1.4 as in the existing hot air nonwoven fabric, it is difficult to eliminate the trade-off relationship between the hand feel and the soft stool permeability only by changing the fineness or fiber density, but the trade-off can be eliminated by being set to 1.4 or less. With regard to the viewpoint, the fiber density ratio of the high-density part and the low-density part is preferably 1.3 or less, more preferably 1.2 or less. The lower limit of the fiber density ratio between the high-density portion and the low-density portion is 1.0, and the closer it is to 1.0, the closer it is to the state where the fiber densities of the high-density portion and the low-density portion are equal, that is, the closer it is to the ideal state in the present invention.
[0036] The lower limit of the strength per unit area weight of the nonwoven fabric of the present invention is not particularly limited, but in order to obtain a nonwoven fabric that does not cause fuzzing or damage, it is preferably 0.40 N / 50 mm or more, more preferably 0.75 N / 50 mm or more, and further preferably 1.00 N / 50 mm or more. In addition, the upper limit of the strength per unit area weight is not particularly limited, but in terms of taking into account the feel of the nonwoven fabric, it is preferably 3.00 N / 50 mm or less, more preferably 2.00 N / 50 mm or less, and further preferably 1.50 N / 50 mm or less.
[0037] The specific volume of the nonwoven fabric is not particularly limited, but is preferably 80 cm 3 / g or more, more preferably 100 cm 3 / g or more, and more preferably 110 cm 3 / g or more. If the specific volume is 80 cm 3 / g or more, the bulkiness of the nonwoven fabric can be satisfied. There is no particular upper limit for the specific volume, but in practice, 300 cm 3 / g or less.
[0038] The weight per unit area of the nonwoven fabric is not particularly limited, but is preferably 15 g / m 2 ~40 g / m 2 If the unit area weight is 15 g / m 2 In addition to sufficient strength, it can also inhibit the backflow of soft stool liquid. If it is 40 g / m 2 Below, the soft stool permeability becomes good.
[0039] In addition to the composite fiber, the nonwoven fabric of the present invention may also include natural fibers (wood fibers, etc.), regenerated fibers (rayon, etc.), semisynthetic fibers (acetate, etc.), or chemical fibers, synthetic fibers (polyester fibers, acrylic fibers, nylon fibers, vinyl chloride fibers, etc.) and other fibers that do not have thermal bonding (hereinafter referred to as "non-thermal bonding fibers"). The so-called "non-thermal bonding fibers" refer to fibers that do not undergo thermal changes (melting or softening) such as those involved in thermal bonding during the thermal bonding process performed when manufacturing the nonwoven fabric. In the case of including non-thermal bonding fibers, as long as the effect of the present invention is not hindered, the proportion of non-thermal bonding fibers relative to the total weight of the nonwoven fabric is not limited, for example, it can be set to 1% by weight to 30% by weight, preferably 3% by weight to 15% by weight. If the proportion of non-thermal bonding fibers is 1% by weight or more, an effect commensurate with the use can be obtained, and if it is 30% by weight or less, a nonwoven fabric that is not easy to fuzz can be obtained.
[0040] The nonwoven fabric of the present invention may include a single (single-layer) nonwoven fabric, or may be laminated with two or more nonwoven fabrics having different fineness, composition, density, etc. In the case of laminating two or more nonwoven fabrics, for example, by laminating nonwoven fabrics having different finenesses, a nonwoven fabric in which the size of the gaps formed between the fibers varies in the thickness direction of the nonwoven fabric is prepared, and the hand feel and soft stool permeability can be controlled. In addition, for example, by laminating nonwoven fabrics having different compositions, a nonwoven fabric in which the hydrophilicity and hydrophobicity vary in the thickness direction of the nonwoven fabric is prepared, and the soft stool permeability can be controlled.
[0041] In addition, the nonwoven fabric of the present invention is not particularly limited, and can be laminated and integrated into nonwoven fabrics or films or sheets other than the nonwoven fabric of the present invention such as hot air nonwoven fabrics, anti-adhesive nonwoven fabrics, meltblown nonwoven fabrics, spunlace nonwoven fabrics, needle-punched nonwoven fabrics, films, mesh sheets, or nets. By laminating and integrating them, soft stool permeability or liquid reflux can be controlled. As a method for laminating and integrating them, there is no particular limitation, and examples include a method for laminating and integrating them by adhesives such as hot melt adhesives, and a method for laminating and integrating them by thermal bonding such as hot air or hot embossing.
[0042] The nonwoven fabric may be subjected to electroplating, water-repellent, hydrophilic, antibacterial, ultraviolet absorbing, near infrared absorbing, or electret processing according to the purpose within a range not impairing the effects of the present invention.
[0043] (Manufacturing method of nonwoven fabric)
[0044] The nonwoven fabric of the present invention is not particularly limited, and includes: a step of forming a web containing composite fibers having a fineness of 3.0 dtex to 6.0 dtex (hereinafter, sometimes referred to as a web forming step), and a step of thermally bonding the intersections of the composite fibers without pressure (hereinafter, sometimes referred to as a thermal bonding step). According to the method, the shape of the web can be maintained, that is, the intersections of the fibers are thermally bonded in a state of less density in the thickness direction and in a manner of achieving a specific fiber density, and a nonwoven fabric having both a soft feel and soft stool permeability can be obtained.
[0045] The web containing the composite fiber is not particularly limited, and may be a long fiber web formed by a debonding method, a meltblowing method, or a tow opening method, or may be a short fiber web (man-made fiber or short-cut fiber), or may be a short fiber web formed by a carding method, an air-laid method, or a wet method. Among them, from the perspective of improving the fluffiness or the hand feel, a web formed by a carding method or an air-laid method is preferred, and a web formed by a carding method is more preferred. In addition, in the present invention, the so-called "web" refers to a fiber aggregate in a state where the fibers are entangled a lot, meaning a state where the intersections of the composite fibers are not connected.
[0046] Then, the intersections of the composite fibers are heat-bonded to the obtained web under non-pressure. The heat medium in the heat bonding process is not particularly limited, and examples thereof include hot air or superheated water vapor. However, in terms of the low fuzzing, excellent hand feel, and productivity of the nonwoven fabric, it is preferred to use superheated water vapor. The heat bonding process may be exemplified by a method in which the web is introduced into a furnace filled with hot air or superheated water vapor gas using a conveyor or the like to continuously obtain the nonwoven fabric.
[0047] The temperature of the heat medium is not particularly limited, and can be exemplified by +0°C to 30°C of the melting point or softening point of the low-melting-point component constituting the composite fiber. In addition, the blowing wind speed of the heat medium is not particularly limited, but in order to make the fiber density ratio of the high-density part to the low-density part of the obtained nonwoven fabric to be 1.4 or less, it is preferably less than 0.1 m / sec. In addition, the blowing pressure of the heat medium is not particularly limited, but in order to make the fiber density ratio of the high-density part to the low-density part of the obtained nonwoven fabric to be 1.4 or less, it is preferably less than 0.1 kPa.
[0048] The treatment time of the thermal bonding step is not particularly limited, but is preferably 60 seconds or less, and more preferably 30 seconds or less. When the treatment time is 60 seconds or less, a nonwoven fabric can be produced with satisfactory productivity.
[0049] The nonwoven fabric of the present invention has both good hand feel and soft stool permeability and is therefore suitable as a surface sheet for absorbent articles.
[0050] Example
[0051] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited thereto. In addition, the measuring methods and definitions of the physical property values shown in the examples are shown below.
[0052] <Fiber fineness of composite fibers>
[0053] The fineness of the composite fiber was measured according to Japanese Industrial Standards (JIS) L 1015.
[0054] <Fiber density in high-density and low-density areas>
[0055] (1) Method for preparing samples for observation
[0056] The nonwoven fabric sample was heated in an oven at 80°C for 5 minutes to reset the stress history of the nonwoven fabric. Then, a photocurable resin (ultra-violet light emitting diode (UV-LED) resin Hoshi no Shizuku [soft] manufactured by PADICO) was fully impregnated into the nonwoven fabric cut into 1 cm (flow direction of the nonwoven fabric: longitudinal direction (machine direction, MD) direction) × 2 cm (width direction of the nonwoven fabric: transverse direction (cross direction, CD) direction), and the photocurable resin was cured by UV irradiation. Then, a microtome (RM2265 manufactured by Leica) was used to cut the cured sample into a thickness of 10 μm in the MD direction, thereby obtaining an observation sample of 10 μm (MD direction) × 2 cm (CD direction).
[0057] (2) Determination of fiber density
[0058] The microtome cut surface of the observation sample was observed at 20 to 50 times using a microscope (VHX-6000 manufactured by KEYENCE) and a polarizing plate, and the number of fibers per area (fibers / mm) was measured at the upper and lower parts of the cut surface divided into three equal parts in the thickness direction. 2 ), the larger value is set as the fiber density of the high-density part, and the smaller value is set as the fiber density of the low-density part. Each fiber density is set as the average value when measured twice.
[0059] <Fiber density ratio between high-density area and low-density area>
[0060] The fiber density ratio of the high-density portion to the low-density portion was calculated by the following formula using the fiber density of the high-density portion and the fiber density of the low-density portion obtained by the above method.
[0061]
[0062] <Weight per unit area>
[0063] The weight of the nonwoven fabric cut into 100 mm × 100 mm pieces was measured, and the value converted per unit area was defined as the unit area weight of the nonwoven fabric (g / m 2 The weight per unit area was taken as the average value of two measurements.
[0064] <Thickness>
[0065] A laser thickness gauge (IL-S065 manufactured by KEYENCE) was used to apply a load of 3.5 g / cm with a 35 mm diameter indenter. 2The thickness at the time of the pressure of was taken as the thickness (mm) of the nonwoven fabric. The thickness was taken as the average value when five locations were measured.
[0066] <Specific volume>
[0067] According to the unit area weight of non-woven fabric (g / m 2 ) and thickness (mm), and calculate the specific volume of the nonwoven fabric using the following formula.
[0068]
[0069] <Strength per unit area weight>
[0070] The maximum strength of a sample cut out in a length of 50 mm × 150 mm in the MD direction when stretched using Autograph (AGX-J) manufactured by Shimadzu Corporation at a chuck distance of 100 mm and a stretching speed of 100 mm / min was defined as the strength of the nonwoven fabric, and the maximum strength was divided by the unit area weight (g / m 2 The value obtained by measuring the strength per unit area weight of the nonwoven fabric is set as the average value when measuring twice.
[0071] <Feel>
[0072] Twenty panelists were asked to touch the nonwoven fabric and score it according to the following criteria, and the feel was evaluated based on the total score.
[0073] (1) Benchmark
[0074] Good: 2 points
[0075] Normal: 1 point
[0076] Bad: 0 points
[0077] (2) Hand feel evaluation
[0078] ◎: Total score is 31 to 40 points
[0079] ○: Total score is 21 to 30 points (current technical level)
[0080] △: Total score is 11 to 20 points
[0081] ×: Total score is 0 to 10 points
[0082] <Soft stool permeability>
[0083] A cylinder with a diameter of 3.5 cm with a mesh attached to the bottom is placed on the central part of the surface of the high-density side of the non-woven fabric, and 8.75 g of artificial soft stool prepared by the following method is flowed into the cylinder. The following time is measured, that is, after the artificial soft stool is injected, the artificial soft stool is transferred to the non-woven fabric through the mesh, and the time until the mesh at the bottom of the cylinder is completely exposed, and the time is used as the liquid flow time. The liquid flow time is set to the average value when measured twice. The shorter the liquid flow time, the more excellent the soft stool permeability.
[0084] Method for preparing artificial soft stool
[0085] The following components (1) to (7) were mixed and stirred, and then diluted with ion exchange water so that the viscosity became 2000 cP, thereby adjusting an artificial stool softener.
[0086] (1) Ion exchange water: 71.9 parts by weight
[0087] (2) Sodium chloride: 1.0 parts by weight
[0088] (3) Glycerin: 15.0 parts by weight
[0089] (4) Sodium carboxymethyl cellulose: 2.0 parts by weight
[0090] (5) Triton X-100: 0.05 parts by weight
[0091] (6) Powdered cellulose: 10.0 parts by weight
[0092] (7) Acid Blue 9: 0.05 parts by weight
[0093] [Example 1]
[0094] As the composite fiber, a concentric sheath-core composite fiber having a fineness of 3.3 dtex and a fiber length of 51 mm was prepared in which polyethylene terephthalate (melting point 250° C.) was arranged on the core and high-density polyethylene (melting point 130° C.) was arranged on the sheath at a volume ratio of 50 / 50.
[0095] Next, a web containing the conjugate fibers was prepared by a carding method, and introduced into a furnace filled with superheated steam at 140° C. for 10 seconds to obtain a nonwoven fabric. The wind speed of the superheated steam gas was less than 0.1 m / sec.
[0096] [Example 2]
[0097] As the composite fiber, a concentric sheath-core composite fiber having a fineness of 4.4 dtex and a fiber length of 51 mm was prepared in which polyethylene terephthalate (melting point 250° C.) was arranged on the core and high-density polyethylene (melting point 130° C.) was arranged on the sheath at a volume ratio of 50 / 50.
[0098] Next, a web containing the conjugate fibers was prepared by a carding method, and introduced into a furnace filled with superheated steam at 140° C. for 10 seconds to obtain a nonwoven fabric. The wind speed of the superheated steam gas was less than 0.1 m / sec.
[0099] [Example 3]
[0100] As the composite fiber, a concentric sheath-core composite fiber having a fineness of 5.6 dtex and a fiber length of 51 mm was prepared in which polyethylene terephthalate (melting point 250° C.) was arranged on the core and high-density polyethylene (melting point 130° C.) was arranged on the sheath at a volume ratio of 50 / 50.
[0101] Next, a web containing the conjugate fibers was prepared by a carding method, and introduced into a furnace filled with superheated steam at 140° C. for 10 seconds to obtain a nonwoven fabric. The wind speed of the superheated steam gas was less than 0.1 m / sec.
[0102] [Example 4]
[0103] As the composite fiber, a concentric sheath-core composite fiber having a fineness of 3.3 dtex and a fiber length of 51 mm was prepared in which polyethylene terephthalate (melting point 250° C.) was arranged on the core and high-density polyethylene (melting point 130° C.) was arranged on the sheath at a volume ratio of 60 / 40.
[0104] Next, a web containing the conjugate fibers was prepared by a carding method, and introduced into a furnace filled with superheated steam at 140° C. for 10 seconds to obtain a nonwoven fabric. The wind speed of the superheated steam was less than 0.1 m / sec.
[0105] [Example 5]
[0106] A web was prepared by a carding method using the same conjugate fibers as in Example 1, and introduced into a furnace filled with heated air at 140° C. for 300 seconds to obtain a nonwoven fabric. The wind speed of the heated air was less than 0.1 m / sec.
[0107] [Comparative Example 1]
[0108] As the composite fiber, a concentric sheath-core composite fiber having a fineness of 2.6 dtex and a fiber length of 51 mm was prepared in which polyethylene terephthalate (melting point 250° C.) was arranged on the core and high-density polyethylene (melting point 130° C.) was arranged on the sheath at a volume ratio of 50 / 50.
[0109] Next, a web containing the conjugate fibers was prepared by a carding method, and introduced into a furnace filled with superheated steam at 140° C. for 10 seconds to obtain a nonwoven fabric. The wind speed of the superheated steam was less than 0.1 m / sec.
[0110] [Comparative Example 2]
[0111] As the composite fiber, a concentric sheath-core composite fiber having a fineness of 6.5 dtex and a fiber length of 51 mm was prepared in which polyethylene terephthalate (melting point 250° C.) was arranged on the core and high-density polyethylene (melting point 130° C.) was arranged on the sheath at a volume ratio of 50 / 50.
[0112] Next, a web containing the conjugate fibers was prepared by a carding method, and introduced into a furnace filled with superheated steam at 140° C. for 10 seconds to obtain a nonwoven fabric. The wind speed of the superheated steam was less than 0.1 m / sec.
[0113] [Comparative Example 3]
[0114] A web was prepared by a carding method using the same conjugate fibers as in Example 1, and the web was treated with hot air at 130° C. and a circulating air velocity of 1.0 m / sec for 10 seconds in a hot air circulation dryer to obtain a nonwoven fabric.
[0115] [Comparative Example 4]
[0116] The same conjugate fibers as in Example 2 were used to prepare a web by a carding method, and the web was treated with hot air at 130° C. and a circulating air velocity of 1.0 m / sec for 10 seconds in a hot air circulation dryer to obtain a nonwoven fabric.
[0117] [Comparative Example 5]
[0118] The same conjugate fibers as in Example 3 were used to prepare a web by a carding method, and the web was treated with hot air at 130° C. and a circulating air velocity of 1.0 m / sec for 10 seconds in a hot air circulation dryer to obtain a nonwoven fabric.
[0119] Table 1 summarizes the production conditions and physical properties of the nonwoven fabrics of Examples 1 to 5.
[0120] [Table 1]
[0121]
[0122] Table 2 summarizes the production conditions and physical properties of the nonwoven fabrics of Comparative Examples 1 to 5.
[0123] [Table 2]
[0124]
[0125] It was found that the fineness of the composite fiber was 3.0 dtex to 6.0 dtex, and the fiber density of the high-density part was 13.0 fibers / mm 2The nonwoven fabrics of Examples 1 to 5, which have a fiber density ratio of 1.4 or less and a fiber density ratio of the high-density part to the low-density part of 1.4 or less, have both hand feel and soft stool permeability. In particular, it is found that the nonwoven fabric of Example 3 has very excellent soft stool permeability while maintaining the same level of hand feel as before. In addition, compared with the case of heating air, Examples 1 to 4 in which the heat medium is superheated water vapor have a higher strength per unit area weight, are less likely to fuzz, and have a shorter processing time. Furthermore, Examples 1 to 3 in which the low-melting point component is 50 volume % have a higher strength per unit area and are extremely less likely to fuzz, compared with Example 4 in which the low-melting point component is 40 volume %.
[0126] On the other hand, the nonwoven fabric of Comparative Example 1, in which the fineness of the composite fiber is reduced compared to Examples 1 to 3, has an excellent hand feel but poor soft stool permeability. This is believed to be because the fiber density in the high-density part exceeds 13.0 fibers / mm due to the use of composite fibers with a small fineness. 2 , resulting in blockage of soft stool. In addition, compared with Examples 1 to 3, the nonwoven fabric of Comparative Example 2 in which the fineness of the composite fiber is increased has excellent soft stool permeability, but the feel is impaired. It is believed that the reason is that: due to the use of composite fibers with large fineness, the friction with the skin becomes greater. Furthermore, Comparative Examples 3 to 5 are nonwoven fabrics obtained under the condition of high wind speed of heated air (existing hot air method) using the same composite fibers as Examples 1 to 3, but the results are: the fiber density ratio of the high-density part to the low-density part is 1.4 or more, the fiber density of the high-density part becomes larger, and the soft stool is blocked. In addition, the feel is also impaired.
[0127] Industrial Applicability
[0128] The nonwoven fabric of the present invention can provide a nonwoven fabric having a simple structure and having both a good texture and soft stool permeability, and can particularly provide a surface sheet for absorbent articles.
Claims
1. A nonwoven fabric comprising composite fibers whose intersections are thermally bonded, wherein the composite fibers have a fineness of 3.0 dtex to 6.0 dtex, and the fiber density of the high-density portion of the nonwoven fabric is 13.0 fibers / mm 2 Hereinafter, the fiber density ratio between the high-density portion and the low-density portion in the nonwoven fabric is 1.4 or less.
2. The nonwoven fabric according to claim 1, wherein The fiber density of the high-density part is 5.5 fibers / mm 2 ~8.0 roots / mm 2 .
3. The nonwoven fabric according to claim 2, wherein: The fineness of the composite fiber is 4.5 dtex to 6.0 dtex.
4. The nonwoven fabric according to claim 3, wherein: The strength per unit area weight of the nonwoven fabric is 1.00 N / 50 mm to 1.50 N / 50 mm.
5. A surface sheet for an absorbent article, comprising the nonwoven fabric according to any one of claims 1 to 4.
6. An absorbent article using the nonwoven fabric according to any one of claims 1 to 4.
Citation Information
Patent Citations
Absorbent article
JP2018068382A
Absorbent article
JP2019080907A
Nonwoven fabric, process for production of nonwoven fabric and absorbent articles
CN101553611A
Patterned non-woven fabric and manufacturing method for same
CN108884615A
Absorbing article
CN109718012A